Data for the paper "Inter-fibre failure of through-thickness reinforced laminates..." - Cui, Hao; Yasaee, Mehdi (Cranfield University, 2018)
Data used in the paper " Hao Cui, Antonio R. Melro, Mehdi Yasaee, Inter-fibre failure of through-thickness reinforced laminates in combined transverse compression and shear load, Composites Science and Technology, 2018 "
Keywords: Through-thickness reinforcement'; 'inter-fibre failue'; 'quasi-static'; 'fracture'; 'Z-pinning'; 'Aerospace Materials'; 'Composite and Hybrid Materials'; 'Mechanical Engineering'